Reconstructing Islamic Legal Epistemology: The Performative Logic of Ijtihād Irshādī in the Lajnah Bahtsul Masā’il of Pesantren Lirboyo - Muhammad Ibtihajuddin; Iffatin Nur; Ahmad Muhtadi Anshor; Asmawi Mahfudz; Rifa'atul Mahmudah (Faculty of Sharia UIN Kiai Ageng Muhammad Besari Ponorogo, 2025)
This article examines the epistemological and performative construction of Ijtihād irshādi at the Lajnah Bahtsul Masail (LBM) of Pesantren Lirboyo as a paradigm that repositions fatwa not merely as juridical determination, but as ethical discourse shaped through communicative, pedagogical, and socially embedded reasoning. Responding to contemporary socio-religious issues such as domestic violence, interfaith marriage, and digital era household needs, this research argues that Ijtihād irshādi emphasises moral orientation, dialogical clarification, and contextual sensitivity while remaining grounded in maqasid al-shariah and the pesantren tradition. Using a qualitative phenomenological case study combined with Foucauldian archaeological discourse analysis, this study examines LBM documents, in-depth interviews with kiai and senior students, and participant observation in bahtsul masail sessions to map the epistemic formation of irshādi fatwas. The findings demonstrate that Irshadi reasoning works through nonimperative ethical guidance, performative enunciation of authority, and flexible interpretive mechanisms that integrate classical texts with lived realities. The study contributes conceptually by clarifying the epistemic structure of irshādi fatwas, methodologically through the synthesis of phenomenology and archaeological analysis, and practically by showing how pesantren-based jurisprudence can guide Muslims through evolving ethical challenges.